Analyzing Gender Inequality and Stereotypes in Foreign-Sourced ELT Textbooks at an Indonesian School: A Mixed-Methods Content Analysis - Swara, Sanditya Jati; Mambu, Joseph Ernest (Universitas Hamzanwadi, 2024)
This study investigates gender stereotypes in two ELT textbooks,